2019
DOI: 10.5935/abc.20190138
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Transcatheter Occlusion with AMPLATZERT AmuletT Device: Real Life Data with Mid-Term Follow-Up Results

Abstract: Background: Left atrial appendage (LAA) occlusion is an alternative therapy for atrial fibrillation patients who have high embolic risk and contraindications to anticoagulant therapy.Objective: To evaluate the feasibility, safety, and mid-term outcomes of percutaneous LAA occlusion, including device-related thrombosis.Methods: Sixty consecutive patients who had undergone percutaneous LAA occlusion with AMPLATZER™ Amulet™ device from September 2015 to March 2018 were enrolled. Patients were followed for 21 ± 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Regarding DRT, the incidence after WATCHMAN implantation was higher in the studies by Aonuma et al [ 14 ] (4.8%) and Xue et al [ 15 ] (4.4%) than in those by Mazzone et al [ 16 ] (2.7%), Boersma et al [ 17 ] (2.8%), and Saw et al [ 18 ] (1%). Three studies on Amulet implantation found a lower incidence of DRT than that reported in studies on WATCHMAN, with Sahinar et al, Landmesser et al and Masoud et al reporting incidence of 0%, 1.6%, and 1.2%, respectively [ 19 21 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding DRT, the incidence after WATCHMAN implantation was higher in the studies by Aonuma et al [ 14 ] (4.8%) and Xue et al [ 15 ] (4.4%) than in those by Mazzone et al [ 16 ] (2.7%), Boersma et al [ 17 ] (2.8%), and Saw et al [ 18 ] (1%). Three studies on Amulet implantation found a lower incidence of DRT than that reported in studies on WATCHMAN, with Sahinar et al, Landmesser et al and Masoud et al reporting incidence of 0%, 1.6%, and 1.2%, respectively [ 19 21 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In total, 2855 patients were included from all studies, and the range of the sample size among the selected studies was 42-1088. Among these, WATCHMAN was used for 1624 patients over five studies [14][15][16][17][18] and Amulet was used for 1231 patients over three studies [19][20][21]. In the DOAC group, a total of 21,200 patients from three studies (with sample sizes between 4838 and 9578 patients) that used rivaroxaban were included [22][23][24].…”
Section: Analyzed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). The lowest incidence of ischemic stroke observed in the included articles was 0 events [ 22 , 28 , 32 , 38 , 43 ] and the highest incidence rates observed were 3.8 per 100 patient-years [ 21 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this issue of the Brazilian Archives of Cardiology, Şahiner et al 14 disclose retrospective data from a center in Turkey, which included 60 patients submitted to implantation of the Amplatzer Amulet device. The main indication for the procedure was the occurrence of bleeding (usually gastrointestinal) in the presence of oral anticoagulation.…”
Section: Referencesmentioning
confidence: 99%